2019
DOI: 10.1029/2019jg005040
|View full text |Cite
|
Sign up to set email alerts
|

Improving Estimates of Gross Primary Productivity by Assimilating Solar‐Induced Fluorescence Satellite Retrievals in a Terrestrial Biosphere Model Using a Process‐Based SIF Model

Abstract: Over the last few years, solar-induced chlorophyll fluorescence (SIF) observations from space have emerged as a promising resource for evaluating the spatio-temporal distribution of gross primary productivity (GPP) simulated by global terrestrial biosphere models. SIF can be used to improve GPP simulations by optimizing critical model parameters through statistical Bayesian data assimilation techniques. A prerequisite is the availability of a functional link between GPP and SIF in terrestrial biosphere models.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 141 publications
2
49
0
1
Order By: Relevance
“…These multispectral and hyperspectral methods are especially amenable to high-throughput analyses and can be incorporated into different HTP platforms such as aerial drones (Sankaran et al, 2015;Kanning et al, 2018), tractors (Scotford and Miller, 2004;Andrade-Sanchez et al, 2014), and carts (Thompson et al, 2018). Previously, SIF had been shown to be correlated with canopy photosynthesis (Yang et al, 2015) and used to estimate gross primary productivity (Bacour et al, 2019). Passive measurements of photosynthetic traits like SIF can be carried out extremely rapidly and at multiple times during the growing season.…”
Section: Solar Induced Fluorescencementioning
confidence: 99%
“…These multispectral and hyperspectral methods are especially amenable to high-throughput analyses and can be incorporated into different HTP platforms such as aerial drones (Sankaran et al, 2015;Kanning et al, 2018), tractors (Scotford and Miller, 2004;Andrade-Sanchez et al, 2014), and carts (Thompson et al, 2018). Previously, SIF had been shown to be correlated with canopy photosynthesis (Yang et al, 2015) and used to estimate gross primary productivity (Bacour et al, 2019). Passive measurements of photosynthetic traits like SIF can be carried out extremely rapidly and at multiple times during the growing season.…”
Section: Solar Induced Fluorescencementioning
confidence: 99%
“…GPP proxies are also used, such as Solar-Induced Fluorescence (Norton et al, 2019;Bacour et al, 2019), isotopic composition of atmospheric CO2 ( 18 : Farquhar et al, 1993;Welp et al, 2011;13 : Peters et al, 2018) and 65…”
Section: Introductionmentioning
confidence: 99%
“…Assimilation of OCO-2 SIF in ORCHIDEE brings the magnitude of both GPP and SIF in closer agreement with observations. This improvement is driven by decreases in leaf photosynthetic capacity (Vcmax, LAImax, leaf age, SLA, Bacour et al, 2019), which decreases the magnitude (but not shape) of APAR closer to observed values (Fig 2), and leads to improvements in GPPyield and SIFyield (Fig 3). Nevertheless, after the assimilation there are still disagreements in SIFyield vs GPPyield relative to the measured quantities ( Fig 6).…”
Section: Insufficient Decline In Sifyield With Aparmentioning
confidence: 66%
“…Adapted to drought stressed Mediterranean species including high temperature correction (Tol et al, 2014;Flexas et al, 2002) BETHY-exp3 Adapted to drought stressed Mediterranean species (Flexas et al, 2002) ORCHIDEE (Bacour et al, 2019) ORCHIDEE-exp1 prognostic Adapted to needleleaf species (Porcar-Castell et al, 2011) and unstressed Mediterranean species (Flexas, 2002), with added dependence on PAR, temperature, and φP Parametric representation of SCOPE (v1.61) to emulate radiative transfer within canopy for PSI/II.…”
Section: Bethy-exp2mentioning
confidence: 99%
See 1 more Smart Citation